Evidence of cascading ecosystem effects following the loss of white sharks from False Bay, South Africa - Neil Hammerschlag; Yakira Herskowitz; Chris Fallows; Thiago B. A. Couto (Frontiers in Marine Science, 2025)

Corrigendum to “A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa” [Biol. Conserv. 284 (2023) 110163] - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

Acoustic tracking of a threatened juvenile shark species, the smooth hammerhead (Sphyrna zygaena), reveals vulnerability to exploitation at the boundary of a marine reserve - Patricia S. Albano; Chris Fallows; Monique Fallows; Lacey H. Williams; Taryn Murray; Oliver Sedgwick; Neil Hammerschlag (Frontiers in Marine Science, 2023)
The coastal waters of South Africa are habitat to a diverse composition of sharks that are vulnerable to exploitation, many of which are endemic and/or classified by the International Union for Conservation of Nature (IUCN) Red List as Threatened or Data Deficient. Accordingly, this region has been identified as a global research and conservation priority for elasmobranchs. The De Hoop Marine Protected Area (MPA), in the Western Cape Province of South Africa, provides 288 km 2 of no-take protection within its boundaries. However, the region experiences heavy commercial fishing, with two vessels actively operating as dedicated shark longliners (as of 2022). When crossing MPA boundaries, sharks are susceptible to capture by these vessels. Utilizing passive acoustic telemetry, the present study evaluated the movements of a threatened juvenile shark species, the smooth hammerhead ( Sphyrna zygaena ), both inside and adjacent to the De Hoop MPA, and along the greater coastline. Movement data from 20 tagged sharks were used to explore the effects of spatial, environmental, and management variables on their residency and movement patterns. Results indicate a high reliance of sharks on unprotected waters immediately adjacent to the MPA’s eastern boundary, an area of high biological productivity due to its proximity to the mouth of an estuary. Although some tagged sharks did move regionally along the South African coastline, individuals spent 95% of their days detected just outside the eastern boundary of the MPA, rendering them vulnerable to commercial shark longlining occurring there. These findings have conservation implications for smooth hammerhead sharks in South Africa and present an opportunity to revisit management practices that may optimize spatial protection for an important life stage of this threatened species.

Sharks as exfoliators: widespread chafing between marine organisms suggests an unexplored ecological role - Lacey H. Williams; Alexandra Anstett; Victor Bach Muñoz; John Chisholm; Chris Fallows; Jonathan R. Green; Jesús Erick Higuera Rivas; Gregory Skomal; Megan Winton; Neil Hammerschlag (Ecology, 2022)

Physiological stress responses to natural variation in predation risk: evidence from white sharks and seals - Neil Hammerschlag; Michael Meÿer; Simon Mduduzi Seakamela; Steve Kirkman; Chris Fallows; Scott Creel (Ecology, 2017)
Predators can impact ecosystems through consumptive or risk effects on prey. Physiologically, risk effects can be mediated by energetic mechanisms or stress responses. The predation‐stress hypothesis predicts that risk induces stress in prey, which can affect survival and reproduction. However, empirical support for this hypothesis is both mixed and limited, and the conditions that cause predation risk to induce stress responses in some cases, but not others, remain unclear. Unusually clear‐cut variation in exposure of Cape fur seals ( Arctocephalus pusillus pusillus ) to predation risk from white sharks ( Carcharodon carcharias ) in the waters of Southwestern Africa provides an opportunity to test the predation‐stress hypothesis in the wild. Here, we measured fecal glucocorticoid concentrations ( fGCM ) from Cape fur seals at six discrete islands colonies exposed to spatiotemporal variation in predation risk from white sharks over a period of three years. We found highly elevated fGCM concentrations in seals at colonies exposed to high levels of unpredictable and relatively uncontrollable risk of shark attack, but not at colonies where seals were either not exposed to shark predation or could proactively mitigate their risk through antipredatory behavior. Differences in measured fGCM levels were consistent with patterns of risk at the site and seasonal level, for both seal adults and juveniles. Seal fGCM levels were not correlated with colony population size, density, and geographic location. Investigation at a high risk site (False Bay) also revealed strong correlations between fGCM levels and temporal variation in shark attack rates, but not with shark relative abundance. Our results suggest that predation risk will induce a stress response when risk cannot be predicted and/or proactively mitigated by behavioral responses.

Effects of lunar phase on predator-prey interactions between white shark (Carcharodon carcharias) and Cape fur seals (Arctocephalus pusillus pusillus) - Chris Fallows; Monique Fallows; Neil Hammerschlag (Environmental Biology of Fishes, 2016)

Effects of environmental conditions on predator–prey interactions between white sharks (Carcharodon carcharias) and Cape fur seals (Arctocephalus pusillus pusillus) at Seal Island, South Africa - Neil Hammerschlag; R. Aidan Martin; Chris Fallows (Environmental Biology of Fishes, 2006)